A Clinicopathological Report of Four Cases of Squamous Odontogenic Tumor-Like Proliferations in Odontogenic Cysts: Suggested Opinions regarding This Unusual Nature - Zargaran, Massoumeh (Case Rep Dent, 2020)
Distinguishing squamous odontogenic tumor-like proliferations (SOTLPs) is important in odontogenic cysts to avoid misinterpretation such as a squamous odontogenic tumor, well-differentiated squamous cell carcinoma, and acanthomatous type of ameloblastoma. This study is aimed at reporting 4 cases of these clinicopathological proliferations in order to shed more light on the importance of distinguishing them from other similar types. 150 odontogenic cysts were studied in which four cases (2.66%) with SOTLPs were identified including 2 radicular cysts, 1 dentigerous cyst, and 1 odontogenic keratocyst. These proliferations were observed in the cysts' wall particularly adjacent to the epithelial lining. All cysts had inflammation while 3 cases showed budding from the epithelial cyst lining. The findings suggested that lining of odontogenic cysts could be a source of SOTLPs, and inflammation probably played an effective role in their development. Its incidence was 2.66% in the present study. Although SOTLPs are not frequent in odontogenic cysts, their identification is important to prevent wrong histopathologic interpretation and treatment.